Mixed method study of feasibility and acceptability of electronic screening for measurement-based symptom monitoring of veterans accessing mental health treatment in VA community care program settings - Erin Almklov; Michael W. Lee; John D. Gault; Brian H. Blanco; Brian Huynh; Abigail Angkaw; Neal Doran; Niloofar Afari; James O. E. Pittman (BMC Health Services Research)
Abstract Background 2022 survey data showed 29% of Veterans utilized Veterans Affairs (VA) paid health care at a non-VA facility, 6% higher than in 2021. Despite an increase in the number of Veterans accessing care in the community via the MISSION Act Community Care Program (CCP), there is limited information on the quality of mental health care delivered to Veterans in these settings. Further, Veterans report barriers to quality care, including poor communication between CCP and VA providers, which can result in negative patient outcomes. We aimed to evaluate the feasibility and acceptability of using electronic screening, eScreening, as part of a process involving remote symptom screening, symptom monitoring, and clinically driven communication from VA to CCP providers, for Veterans accessing mental health treatment in CCP settings. Methods Veterans (n = 150) diagnosed with major depressive disorder, an anxiety disorder, post-traumatic stress disorder, and/or an adjustment disorder referred to mental health care in CCP between August-November 2021 were eligible to participate. Veterans received an eScreening link to complete an initial web-based assessment and three follow-up assessments spaced 4–6 weeks apart over the course of their treatment. Quantitative assessment data was largely characterized using descriptive statistics and included patient-reported outcome (PRO) measures (PTSD and depression), health-related quality of life/functioning, community care information (e.g., number of sessions attended), and satisfaction with the eScreening technology. Qualitative interview data was also collected from participating Veterans and CCP providers to better understand experiences with eScreening. Results Findings support the feasibility and acceptability of using eScreening to administer and monitor PROs for Veterans accessing mental health treatment in CCP. Of the Veterans who provided eScreening satisfaction ratings (Ns = 45–55), 89% had no technical difficulties; 78% felt comfortable entering personal information; and 83% were neutral or positive about ease of use. Focus group interviews revealed strong support from Veterans, who stated the software was easy to use; they felt comfortable completing PRO measures; and they appreciated having their symptoms monitored. Similarly, providers indicated eScreening had a positive impact on communication, collaboration of care, and transparency. Conclusions Technologies like eScreening represent a promising tool to support the mental health care Veterans receive when they access CCP.